The origin of long-chain fatty acids required for de novo ether lipid/plasmalogen synthesis - Serhii Chornyi; Rob Ofman; Janet Koster; Hans R. Waterham (Journal of Lipid Research, 2023)
Peroxisomes are single-membrane bounded organelles that in humans play a dual role in lipid metabolism, including the degradation of very long-chain fatty acids and the synthesis of ether lipids/plasmalogens. The first step in de novo ether lipid synthesis is mediated by the peroxisomal enzyme glyceronephosphate O-acyltransferase, which has a strict substrate specificity reacting only with the long-chain acyl-CoAs. The aim of this study was to determine the origin of these long-chain acyl-CoAs. To this end, we developed a sensitive method for the measurement of de novo ether phospholipid synthesis in cells and, by CRISPR-Cas9 genome editing, generated a series of HeLa cell lines with deficiencies of proteins involved in peroxisomal biogenesis, beta-oxidation, ether lipid synthesis, or metabolite transport. Our results show that the long-chain acyl-CoAs required for the first step of ether lipid synthesis can be imported from the cytosol by the peroxisomal ABCD proteins, in particular ABCD3. Furthermore, we show that these acyl-CoAs can be produced intraperoxisomally by chain shortening of CoA esters of very long-chain fatty acids via beta-oxidation. Our results demonstrate that peroxisomal beta-oxidation and ether lipid synthesis are intimately connected and that the peroxisomal ABC transporters play a crucial role in de novo ether lipid synthesis.